Epithelial CD80 promotes immune surveillance of colonic preneoplastic lesions and its expression is increased by oxidative stress through STAT3 in colon cancer cells - Marchiori, Chiara (J Exp Clin Cancer Res, 2019)
BACKGROUND: One of the most potent costimulatory molecules involved in the recognition and killing of tumor cells is CD80. However, its role and the molecular mechanisms regulating its expression in sporadic colorectal carcinogenesis remain elusive. Here, we provide evidence for CD80 overexpression in human colon epithelial cells derived from preneoplastic mucosa. METHODS: Expression of CD80 on colonic epithelial cells isolated from normal human colonic mucosa, preneoplastic and neoplastic specimens was assessed by flow cytometry. WT and CD80KO mice received azoxymethane to induce colon preneoplastic lesions and sacrificed to perform histology, flow cytometry analysis and immunohistochemistry of colonic mucosa. Some WT mice were treated with a monoclonal anti-CD80 antibody following AOM administration. Primary colon epithelial cells and CT26 cell line were used to quantify the expression of CD80 in response to pro-oxidant stimuli. Specific pharmacological inhibitors and siRNA silencing were used to inhibit MAPK pathways and STAT3. RESULTS: CD80 expression was significantly increased in colon epithelial cells of human preneoplastic lesions. In the AOM model, CD80 impairment by administration of neutralizing antibodies or use of CD80 knockout mice enhanced dysplasia development. In vitro, CD80 upregulation was induced by oxidative stress in colon cancer cells and primary colon epithelial cells. In addition, reactive oxygen species could induce CD80 expression via the JNK and p38 MAPK pathways, that activated STAT3 transcription factor in colon cancer epithelial cells. CONCLUSION: This study provide evidence for a major role of CD80 in orchestrating immune surveillance of colon preneoplastic lesions and might help to develop novel approaches that exploit anti-tumor immunity to prevent and control colon cancer. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13046-019-1205-0) contains supplementary material, which is available to authorized users.